2015
DOI: 10.1016/j.physbeh.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Psychological or physical prenatal stress differentially affects cognition behaviors

Abstract: Results of our study revealed that prenatal physical or psychological stress have different effects on motor and cognitive functions of the offspring. Male and female offspring were differentially affected by prenatal stress. We suggest more studies to evaluate the role of sex hormones on the effects of prenatal physical or psychological stress on cognitive and motor functions of the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
5
40
0
3
Order By: Relevance
“…Specifically, in models of prenatal stress, some have observed selective impairments in female BalbC mouse offspring (Wang et al., 2011) while others found a male bias in impairments in various species of rats (Mueller and Bale, 2007, Salomon et al., 2011, Schulz et al., 2011, Wang et al., 2016) using the NOP or Morris water maze tasks in adolescence or adulthood. Still other studies using either mice and rats as model systems, failed to find any sex differences (Benoit et al., 2015, Nazeri et al., 2015) or showed ELS to be associated with improvements in cognitive performance (Zuena et al., 2008, Barbie-Shoshani et al., 2016). Studies investigating the effects of early postnatal stress manipulations on cognitive outcomes have been less numerous and have similarly resulted in disparate findings, that appear to depend upon the specific timing and form of stress used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in models of prenatal stress, some have observed selective impairments in female BalbC mouse offspring (Wang et al., 2011) while others found a male bias in impairments in various species of rats (Mueller and Bale, 2007, Salomon et al., 2011, Schulz et al., 2011, Wang et al., 2016) using the NOP or Morris water maze tasks in adolescence or adulthood. Still other studies using either mice and rats as model systems, failed to find any sex differences (Benoit et al., 2015, Nazeri et al., 2015) or showed ELS to be associated with improvements in cognitive performance (Zuena et al., 2008, Barbie-Shoshani et al., 2016). Studies investigating the effects of early postnatal stress manipulations on cognitive outcomes have been less numerous and have similarly resulted in disparate findings, that appear to depend upon the specific timing and form of stress used.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have reported significant impairment following various forms of ELS on spatial learning in female rats (Marco et al., 2013; Wang et al., 2016), while others found a male bias in impairment in both mice and rats ( Barha et al., 2007; Mueller and Bale, 2007; Salomon et al., 2011; Schulz et al., 2011; Wang et al., 2011; Naninck et al., 2015). Other studies from both mice and rats failed to identify sex differences in performance (Benoit et al., 2015; Nazeri et al., 2015), while further studies in rats found ELS to be associated with improved cognitive performance (Barha et al., 2007; Zuena et al., 2008; Uysal et al., 2012; Barbie-Shoshani et al., 2016). Thus, considerable confusion exists with regard to the effects of ELS on cognitive functioning, possibly due to the varied forms of stress, timing of stress implementation, and age at testing.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be explained by the type of stressor used in this study, due to its larger intensity as compared to other stressors [24]. Other studies report that PS induced by a physical stressor affects one-month-old rats of both sexes, but psychological stressors only affect males [21]. These authors suggest that increased cognitive ability in PS females as compared to that in PS males may be explained by the neuroprotective effect of estrogens in females, which makes females less susceptible to present cognitive disorders.…”
Section: Discussionmentioning
confidence: 83%
“…In three-month-old animals PS by immobilization [20], and two-month-old animals PS by a variety of short-term stressors (immobilization, forced swimming, and permanence on an elevated platform) [18], during the last gestational week, altered learning in male rats, but not in female, was reported. Another study showed that maternal physical stress deteriorates spatial learning and memory in rats of both sexes at 40 days of postnatal life, but maternal psychological stress only affects males [21]. Different results among studies may be explained in terms of the diverse protocols for PS used (varying in duration, intensity or gestational period) and/or the age of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Los animales se mantuvieron en condiciones controladas de temperatura (20-25°C) y en ciclos invertidos de 12 horas una temperatura de 21±2°C. La piscina se dividió en cuatro cuadrantes imaginarios (noreste NE, noroeste NO, sureste SE, suroeste SO) iguales tomando como referencia la zona de acceso al laberinto, al liberar al sujeto para la realización de la prueba se lleva a cabo desde diferentes puntos de partida en cada repetición así como en cada día y tres figuras que se colocaron en las paredes blancas alrededor de la tina, las cuales funcionaron como pistas espaciales dentro de la piscina también Latencia de escape, que hace referencia al tiempo que tardan las ratas en encontrar la plataforma sumergida durante la fase de aprendizaje y en las memorias de corto y largo plazo y en las sesiones en las que se retiró la plataforma (día 7) de la piscina se evaluó: el tiempo de permanencia en el cuadrante que es el tiempo que la rata se encuentra en el cuadrante en donde estuvo la plataforma y el número de cruces de la rata sobre la zona donde anteriormente se encontraba la plataforma durante la fase de aprendizaje(60,90). De manera esquemática se ejemplifican el laberinto acuático de Morris el cual está conformado de tres pistas espaciales alrededor de la tina, la división imaginaria de los cuadrantes (noreste NE, noroeste NO, sureste SE, suroeste SO) así como la posición de la plataforma en uno de los cuadrantes (NO).…”
unclassified